How to read a financial report : wringing vital signs out of the numbers - Tracy, John A. (Wiley, 2009)
How to Read a Financial Report Seventh Edition. Financial reports provide vital information to investors, lenders, and managers. Yet, the financial statements in a financial report seem to be written in a foreign language that only accountants can understand. This Seventh Edition of How to Read a Financial Report breaks through the language barrier, clears away the fog, and offers a plain-English user's guide to financial reports. The book helps you get a sure-handed grip on the profit, cash flow, and financial condition of any business. Here's what's new in the Seventh Edition:.:. ; . Discussi.